Effects of Different Straw Return Methods on Farmland Carbon Footprint and Water Footprint - Lu Hua; Yang Gao; Dingyang Li; Zhenxing Yang; Zhiping Liu (Agriculture)
Straw return is an effective agricultural measure that influences the ecological environment. In the context of global climate change and the need for sustainable development, it is essential to explore how straw return methods affect the environment. This study conducted a two-year field experiment comparing different straw return treatments: no straw return (CK), straw return directly (SR), and straw returned in deep ditches (ISR). The results showed that SR treatment increased soil dissolved organic carbon (DOC) (21.7~25.8%) and dissolved organic nitrogen (DON) (8.5~43.8%) compared to CK. The ISR treatment significantly enhanced DOC (13.1~33.0%) and DON (14.2~50.8%). Both SR and ISR treatments also improved maize growth indicators, such as leaf area index (LAI), stem biomass, leaf biomass, and grain biomass. In terms of environmental effects, the ISR measure reduced N2O emissions and significantly lowered the carbon footprint (CF) and water footprint (WF). Specifically, the yield-scale carbon footprint (CFy) and yield-scale water footprint (WFy) of ISR were reduced by 12.0% and 9.1%, respectively, in 2023. Correlation analysis revealed that soil DON and DOC were key factors in these environmental benefits. Furthermore, the reduction in WF and CF was closely linked to the increased SWC and higher biomass in all maize organs. Therefore, we demonstrated that the ISR measure not only promotes maize biomass accumulation but also effectively mitigates carbon emissions and water consumption on farmland. It may be related to the boosting soil DON and DOC levels. Overall, the ISR method holds promise for supporting sustainable farming practices.